Breeding of the Giant African Edible Snail (Achatina achatina Linnaeus, 1758) in Gbado-Lite city, Democratic Republic of the Congo - Koto-te-Nyiwa Ngbolua; Ruphin Djoza Djolu; Michael Dibere Selenga; Jean-Bernard Bosanza Zanyako; Colette Masengo Ashande; Clarisse Mawi Falanga; Moises Mawunu Monizi; Jonas Mbongu Sodi Nagahuedi (Britain International for Academic Research (BIAR) Publisher, 2022)
The objective of this study was to evaluate the effect of the nature of the food ration on the size, weight, weight gain and ex situ reproduction of the snail (Achatina achatina) in Gbado-Lite. The results of this work show that variations in size [from 8.2±1.2 cm at feeding (D0) to 9.9±2.1 cm at day D84 (snail farm A) and from 8.4±1.1 cm to 10.2±1.8 cm (snail farm B)]; hatching rate [88.2% (snail house A) and 94.2% (snail house B)]; weight [460±18.5 g at loading (D0) to 760±26.3 g on day D84 (snail house A) and 475±10.9 g to 760±26.3 g (snail house B)]; mean absolute weight gain 84 days after loading [37.7±12.0 g (snail house A) and 36.5±9.6 g (snail house B)] were not statistically different between snail houses including mean daily weight gain (0.450±0.1 g/d vs. 0.363±0.1 g/d) and survival rate (90% vs. 100%). Both formulations have the same effect on the reproduction of Achatina achatina in captivity. It is therefore desirable that more in-depth studies be conducted with the aim of popularizing this non-conventional breeding in the city of Gbado-Lite. Thus, in the current context of biodiversity erosion linked to human activities as well as environmental factors, snail farming can contribute to empowerment, improved socio-economic conditions and household resilience to climate change.